The sheddase ADAM10 is a potent modulator of prion disease - Hermann C Altmeppen; Johannes Prox; Susanne Krasemann; Berta Puig; Katharina Kruszewski; Frank Dohler; Christian Bernreuther; Ana Hoxha; Luise Linsenmeier; Beata Sikorska; Pawel P Liberski; Udo Bartsch; et al. (eLife, 2015)
The prion protein (PrPC) is highly expressed in the nervous system and critically involved in prion diseases where it misfolds into pathogenic PrPSc. Moreover, it has been suggested as a receptor mediating neurotoxicity in common neurodegenerative proteinopathies such as Alzheimer's disease. PrPC is shed at the plasma membrane by the metalloprotease ADAM10, yet the impact of this on prion disease remains enigmatic. Employing conditional knockout mice, we show that depletion of ADAM10 in forebrain neurons leads to posttranslational increase of PrPC levels. Upon prion infection of these mice, clinical, biochemical, and morphological data reveal that lack of ADAM10 significantly reduces incubation times and increases PrPSc formation. In contrast, spatiotemporal analysis indicates that absence of shedding impairs spread of prion pathology. Our data support a dual role for ADAM10-mediated shedding and highlight the role of proteolytic processing in prion disease.